DISSEMINATION OF INFORMATION AS AN OBJECT OF LAW - Dzhenakova Ekaterina (Электронное приложение к Российскому юридическому журналу)
Based on the analysis of legal conceptions of an object of legal relationship, objects of information relationships are determined. The latter are considered as structural objects consisting of one or several substantive elements. Consequently, dissemination of information is presented in two respects: as a simple legal relation, object of which is the dissemination activity itself, and as a complex legal relation, object of which consists of disseminator’s and recipient’s interests covering the actions for disseminating and receiving information, the information and telecommunication resources, and the contents of information. Thus, dissemination of information is defined as a legal relationship with a complicated structure, and this allows to specify the limits of information dissemination, to define the list of subjects of dissemination, their capacities and legal nature